DO MSME’S BORROW RATIONALLY? BEHAVIORAL BIASES, CREDIT DECISIONS, AND FINANCIAL MANAGEMENT EFFECTS - Putu Satya Dadi Saputra; Desak Nyoman Sri Werastuti; I Gusti Ayu Purnamawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The phenomenon shows that the level of non-performing loans (NPL) among MSMEs in Buleleng Regency remains relatively high compared to the provincial average, indicating issues in the quality of financing decision-making, while many MSME actors continue to take credit despite suboptimal financial management capabilities, suggesting that financial decisions may be more influenced by psychological factors than data-based rational analysis. This study aims to analyze the effect of illusion of control and regret aversion on credit decision-making with financial management as a moderating variable among MSMEs in Buleleng Regency. The research employed a quantitative associative approach with data collected through questionnaires from 100–200 MSME actors and analyzed using SEM-PLS. The results show that illusion of control has a positive and significant effect on credit decision-making, whereas regret aversion has no significant effect. In addition, financial management is not proven to moderate the relationship between these psychological variables and credit decisions. These findings confirm that certain cognitive biases may be more dominant than financial management capability in influencing business financing decisions. This study contributes theoretically to behavioral finance literature in the MSME context and provides practical implications for financial institutions and policymakers to consider psychological aspects in credit education strategies and proper financial management practices as a basis for deciding to take credit.